(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
The technological acceleration is constantly revolutionizing liveness, allowing a high degree of performativity to emerge even in simple everyday multimedia habits. The pervasive ubiquity of digital media profoundly influences how performance is delivered and experienced. By activating effective dynamics of audience involvement, tools such as live streaming, virtual and augmented reality, artificial intelligence, mapping and interaction design now make it possible to create multimedia experiences that offer a whole social and communicative dimension, characterized by a transdisciplinary and post-anthropocentric approach. Therefore, live media performance should be considered a specific field of artistic production and investigation, in which different formats and practices can be included. The electronic agents on stage are designed to convey a sense of deep interconnection between the performers, the audience and everything around them. The scene thus becomes a suspended dimension, a synaesthetic and immersive “place of the mind” in which reality is reconstructed as the result of not-just-human action. In this sense, the technosphere becomes a working partner. Through the analysis of key research and artistic experiences of this disciplinary field, a transdisciplinary post-anthropocentric and post-human interpretative perspective will be proposed, focusing on both human and non-human forms of action and expressive gesture.